2003
DOI: 10.1177/0095798403029002003
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Value Orientations and Accommodation among Heterosexual Relationships in Jamaica

Abstract: In this study, we tested the following hypotheses concerning cultural value orientations as predictors of accommodation among heterosexual relationships in Jamaica: (a) Individuals' Group Orientation will be a significant positive predictor of Accommodation toward opposite-sex relationship partners, whereas (b) individuals' Self Orientation will not be significantly related to Accommodation toward opposite-sex relationship partners. A total of 287 individuals (44 males, 233 females, and 10 unspecified) partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Overall, we believe that the strengths outweigh the shortcomings in the present study. First, not only was the reliability of the individualism scale in the present study similar to reliabilities obtained for the same scale in previ-ous studies outside the United Kingdom (e.g., Gaines et al, in press;Gaines et al, 2003), but the same individualism scale was used by , whose results were (re)interpreted by Coon and Kemmelmeier (2001) as supporting the claim that within the United States, persons of African descent are the most individualistic of all. Second, in several instances (especially when comparing the results of African-descended versus Europeandescended persons), the lower-than-expected ability to detect genuine effects (i.e., power) was offset by a low likelihood of rejecting the null hypotheses when it should not have been rejected (i.e., alpha; see Cohen et al, 2003).…”
Section: Strengths and Limitations Of The Present Studysupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, we believe that the strengths outweigh the shortcomings in the present study. First, not only was the reliability of the individualism scale in the present study similar to reliabilities obtained for the same scale in previ-ous studies outside the United Kingdom (e.g., Gaines et al, in press;Gaines et al, 2003), but the same individualism scale was used by , whose results were (re)interpreted by Coon and Kemmelmeier (2001) as supporting the claim that within the United States, persons of African descent are the most individualistic of all. Second, in several instances (especially when comparing the results of African-descended versus Europeandescended persons), the lower-than-expected ability to detect genuine effects (i.e., power) was offset by a low likelihood of rejecting the null hypotheses when it should not have been rejected (i.e., alpha; see Cohen et al, 2003).…”
Section: Strengths and Limitations Of The Present Studysupporting
confidence: 87%
“…Participants completed five 10-item scales, measuring the cultural values of individualism, collectivism, familism, romanticism, and spiritualism that were developed by Gaines (e.g., Gaines et al, in press;Gaines, Ramkissoon, & Matthies, 2003). Each item was scored according to a 5-point Likert-type scale from 1 (disagree strongly) to 5 (agree strongly) such that higher scores reflected higher levels of internalization of the cultural value in question.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, if in the U.S. the 'we-values' (i.e., collectivism, familism, romanticism, and spiritualism) were positively and significantly related to accommodation, the 'me-value' of individualism showed neither positive nor significant correlation with accommodation (Gaines et al, in press). In Jamaica, however, individualism was a negative and significant predictor of accommodation, whereas the 'we-values' were not related to accommodation (Gaines, Ramkissoon, & Matthies, 2003). Gaines and colleagues (2003) proposed that the difference between the results in the U.S. versus in Jamaica reflected the difference in the salience of cultural values in two cultures.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…The one study that explored heterosexual relationships (Gaines, Ramkissoon, & Matthies, 2003) explored the associations between group orientations, which they termed cultural value orientations, and reactions in dilemmas with partners. The researchers found that individualism (as opposed to what they termed group orientations and which included collectivism, familism, romanticism, and spirituality) was negatively associated with reports of accommodation in relationships.…”
Section: Summary Of Review Findingsmentioning
confidence: 99%
“…Theories or conceptual frameworks were used or referenced in four of these seven studies. Interdependence theory of social relations (H. H. Kelley & Thibaut, 1978) and cultural value orientations (Triandis, 1995) were used in the Gaines et al (2003) article. In two studies, although not used for explicit hypothesis testing, theories were mentioned.…”
Section: Summary Of Review Findingsmentioning
confidence: 99%